Optimalisasi Pencegahan Covid-19 Melalui Pemanfaatan Wastafel Sensorik dan Pemberdayaan Ekonomi Masyarakat Berbasis Tanaman Lokal di Desa Pejambon Kecamatan Sumberrejo Kabupaten Bojonegoro - Shiddiqi, Hasbi Ash; Sa'ida, Ita Aristia (Proceedings of Annual Conference on Community Engagement, 2022)
The outbreak of Corona Virus Disease 2019 (Covid-19) has had an extraordinary impact on the global economy in 2020. Covid-19, which first appeared in Wuhan, China, in December 2019, spread very quickly to 178 countries or 99 .5% of world GDP. The companion team is here to create a program that is in accordance with the problems faced by Pejambon Village with the theme Optimizing Covid-19 Prevention Through the Use of Sensory Sinks and Local Plant-Based Community Economic Empowerment in Pejambon Village, Sumberrejo District, Bojonegoro Regency. This assistance uses an Asset Based Community Development (ABCD) approach, which prioritizes the utilization of existing assets and potentials in Pejambon village. The activity of making Sensory Sinks is one of the main programs carried out by the KKN group in Pejambon village. This activity was piloted several times at the Pejambon village hall and in front of the Poskesdes office. After the tool was successfully tested, it was launched on April 1, 2021 with village officials and community leaders from Pejamon village who were explained by the companion team on how to use the Sensory Sink without touching the faucet. The training activity for making crackers and chips from the luntas plant was attended by PKK cadres in Pejambon Village. These snacks are foods that come from natural ingredients and are easy to find in the Pejambon Village environment from luntas which can be beneficial for the body. This luntas plant is often found around the houses of Pejambon Village residents, which are generally made for daily ointment